Shrub tundra ecohydrology: rainfall interception is a major component of the water balance - Simon Zwieback; Qianyu Chang; Philip Marsh; Aaron Berg (Environmental Research Letters, 2019)
As shrubs expand across the Arctic, they alter all cycles in the Earth system, including the water cycle. However, the coupling of shrubs with the water cycle during summer remains poorly understood. Rainfall interception, a major cause of divergent hydrological responses between vegetated and non-vegetated environments, is particularly poorly constrained. We quantified shrub rainfall interception and redistribution in birch and alder in the Western Canadian Arctic using networks of throughfall and stemflow gauges. We find that rainfall interception losses are a major component of the water budget, as effective rainfall was reduced by 15%–30% in the birches. Underneath alders, effective rainfall was almost as large or larger than gross rainfall, but they also left a rain shadow. The spatial variability in throughfall was substantial underneath both shrub species. Stemflow was a small but non-negligible component, as the alders concentrated ∼15% of rainfall to their few vertical stems, compared to the ∼8% the birches funnelled along their numerous, predominantly skewed stems. The substantial small-scale variability in effective rainfall may create islands in which conditions for certain biogeochemical processes are particularly favourable. On larger scales, rainfall interception reduces the water yield and thus the runoff received by downstream ecosystems such as lakes. The interception losses are predicted to increase with shrub density in a way that also depends on climatic conditions, with large losses in many coastal environments. The extent to which shrub expansion leads to drier Arctic ecosystems is, however, unclear because of the complex interplay between many ecohydrological processes. Shrub rainfall interception is one major, previously overlooked piece of this puzzle.